Factors Influencing the Kinetics of Esterification of Fatty Acids over Solid Acid Catalysts - Satyarthi, Jitendra Kumar; Radhakrishnan, Sambhu; Srinivas, Darbha (Energy & Fuels, 2011)
The kinetics of esterification of fatty acids with alcohols over three different solid acid catalysts, viz., large pore zeolite-beta (H beta), micro-mesoporous Fe-Zn double-metal cyanide (DMC), and mesoporous Al-MCM-41, have been reported. Hydrophobicity of these catalysts increases in the order: Al-MCM-41 < H beta < DMC. The chain lengths of the fatty acid (C(8.0)-C(18.1)) and alcohol (C(1)-C(8)) molecules have been varied, and their influence on kinetic parameters has been studied. The present study reveals that porosity and surface hydrophobicity of the catalyst are the two important factors other than acid properties (concentration and strength of acid centers) that influence the esterification reaction.